Influence of diet with different lipid composition on neutrophil chemiluminescence and disease activity in patients with rheumatoid arthritis. - Magaro, M (1988)
Neutrophil chemiluminescence was determined in patients with active rheumatoid arthritis. Twelve patients were randomly assigned either to a diet high in polyunsaturated fatty acids supplemented with eicosapentaenoic and docosahexaenoic acids or to a diet high in saturated fatty acids. A correlation with clinical and laboratory parameters is also reported. No statistical difference was observed in neutrophil chemiluminescence and in clinical parameters in the group of patients treated with a diet high in saturated fatty acids. Fish oil ingestion resulted in subjective alleviation of active rheumatoid arthritis and reduction of neutrophil chemiluminescence. This study corroborates the hypothesis of an anti-inflammatory role for polyunsaturated fatty acids in patients with chronic inflammatory diseases.